Forming megakaryocytes from murine induced pluripotent stem cells by the inducible overexpression of supporting factors. Issue 1 (3rd December 2020) - Cullmann, Katharina; Jahn, Magdalena; Spindler, Markus; Schenk, Franziska; Manukjan, Georgi; Mucci, Adele; Steinemann, Doris; Boller, Klaus; Schulze, Harald; Bender, Markus; Moritz, Thomas; Modlich, Ute
Abstract: Background: Platelets are small anucleate cells that circulate in the blood in a resting state but can be activated by external cues. In case of need, platelets from blood donors can be transfused. As an alternative source, platelets can be produced from induced pluripotent stem cells (iPSCs); however, recovered numbers are low. Objectives: To optimize megakaryocyte (MK) and platelet output from murine iPSCs, we investigated overexpression of the transcription factors GATA‐binding factor 1 (GATA1); nuclear factor, erythroid 2; and pre–B‐cell leukemia transcription factor 1 (Pbx1) and a hyperactive variant of the small guanosine triphosphatase RhoA (RhoAhc). Methods: To avoid off‐target effects, we generated iPSCs carrying the reverse tetracycline‐responsive transactivator M2 (rtTA‐M2) in the Rosa26 locus and expressed the factors from Tet‐inducible gammaretroviral vectors. Differentiation of iPSCs was initiated by embryoid body (EB) formation. After EB dissociation, early hematopoietic progenitors were enriched and cocultivated on OP9 feeder cells with thrombopoietin and stem cell factor to induce megakaryocyte (MK) differentiation. Results: Overexpression of GATA1 and Pbx1 increased MK output 2‐ to 2.5‐fold and allowed prolonged collection of MK. Cytologic and ultrastructural analyses identified typical MK with enlarged cells, multilobulated nuclei, granule structures, and an internal membrane system. However, GATA1 and Pbx1 expression did not improve MK maturation or platelet release, although in vitro–generated platelets were functional in spreading on fibrinogen or collagen‐related peptide. Conclusion: We demonstrate that the use of rtTA‐M2 transgenic iPSCs transduced with Tet‐inducible retroviral vectors allowed for gene expression at later time points during differentiation. With this strategy we could identify factors that increased in vitro MK production. Abstract :